A portable 3-d imaging FMCW MIMO radar demonstrator with a 24 × 24 antenna array for medium-range applications - Alexander Ganis and Enric Miralles Navarro and Bernhard Schoenlinner and Ulrich Prechtel and Askold Meusling and Christoph Heller and Thomas Spreng and Jan Mietzner and Christian Krimmer and Babette Haeberle and Steffen Lutz and Mirko Loghi and Angel Belenguer and Hector Esteban and Volker Ziegler (IEEE transactions on geoscience and remote sensing, 2018)
Multiple-input multiple-output (MIMO) radars have been shown to improve target detection for surveillance applications thanks to their proven high-performance properties. In this paper, the design, implementation, and results of a complete 3-D imaging frequency-modulated continuous-wave MIMO radar demonstrator are presented. The radar sensor working frequency range spans between 16 and 17 GHz, and the proposed solution is based on a 24-transmitter and 24-receiver MIMO radar architecture, implemented by time-division multiplexing of the transmit signals. A modular approach based on conventional low-cost printed circuit boards is used for the transmit and receive systems. Using digital beamforming algorithms and radar processing techniques on the received signals, a high-resolution 3-D sensing of the range, azimuth, and elevation can be calculated. With the current antenna configuration, an angular resolution of 2.9° can be reached. Furthermore, by taking advantage of the 1-GHz bandwidth of the system, a range resolution of 0.5 m is achieved. The radio-frequency front-end, digital system and radar signal processing units are here presented. The mediumrange surveillance potential and the high-resolution capabilities of the MIMO radar are proved with results in the form of radar images captured from the field measurements.
Keywords: 3-D; Digital beamforming (DBF); Frequencymodulated continuous wave (FMCW); Multiple-input multipleoutput (MIMO); Printed circuit boards (PCBs); Radar; Time-division multiplexing (TDM)